A informação científica: sua disseminação, interação informal e seus efeitos nos participantes de uma reunião anual de cientistas sociais brasileiros - Maciel, Alba Costa (1982)
Study of dissemination of scientific information, informal interaction and the impact of this information received by attendants from an annual scientific meeting in Social Sciences in Brazil The following topics are analyzed: professionals attending the meeting, their academic background, their place of work, papers presented, length of time, nature of presentations, dissemination, relevance, as well as the most active institutions and the regionalism of the research in this area Channels utilized by social scientists participants in the communication system outlined, during and after the meeting and the communication problems that they encountered during the meeting are also analyzed in this paper.